Modulation doping of quantum dot laser active area and its impact on lasing performance. (October 2015) - Konoplev, S S; Savelyev, A V; Korenev, V V; Maximov, M V; Zhukov, A E
Abstract: We present a theoretical study of modulation doping of active region in the quantum dot (QD) laser and corresponding issues of QD charge neutrality violation, a band diagram of the laser and charge carriers distribution in the structure. Modulation doping is discussed as a possible technique to control laser output characteristics. It was shown that modulation doping leads to an increase of threshold current of lasing through excited QD optical transition together with power emission from QD ground state.